STRATEGI PERGURUAN TINGGI DALAM MENINGKATKAN PUBLIKASI HASIL PENELITIAN - Hamdan Sugilar; Tedi Priatna; Wahyudin Darmalaksana (IAIN Batusangkar, 2019)
Research without the publication has not provided meaning about benefits and research results. Research results need to be published or disseminated to benefit the community. The purpose of this study is to determine the strategy of universities in the acceleration of publication of research results. The research method used a qualitative approach. Sources of data consist of interviews with lecturers and team of journal publications, document studies, and reports on the achievements of publications of scientific papers. This study uses inductive thinking. This research was conducted on journal team and publication of Universitas Pendidikan Indonesia and research and publishing institute of UIN Sunan Gunung Djati Bandung. Based on the research obtained the following results: Universities make strategic plans and master plan research in achieving publication of research results; to form journal team and publication and term of reference (TOR) publication of research result